Social Norms and Misinformation: Experimental Evidence on Learning about Menstrual Health Management in Rural Bangladesh - Silvia Castro; Kristina Czura (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Inadequate hygiene during menstruation can have severe consequences, such as adverse health effects, lower educational attainment and higher work absenteeism. Cultural taboos and social norms surrounding menstruation may contribute to misinformation about menstrual hygiene and may also interfere with attempts to improve knowledge. Using lab-in-the-field experiments with women in rural Bangladesh, we measure social norms in the form of empirical and normative expectations about menstrual health and hygiene explicitly, and relate them to behavior and knowledge. We then provide an information intervention on menstrual health and hygiene and observe how this changes the perceived social norms. We find that the majority of women report decreased physical and mental well-being, in particular stress and shame, during their menstruation. Further, we find knowledge gaps on the proper use of hygienic material for menstrual health management and that empirical and normative expectations are well matched to reported adverse health behavior. The information intervention helps to correct harmful social norms, although results are more pronounced for women who have more autonomy and agency over their own decisions.
Keywords: I12; I15; D91; O12; 330; social norms; menstrual health management; menstrual hygiene; information; adverse health behavior